Mencermati Eksistensi Pelayanan Sektor Publik: Pergeseran Paradigma, Tantangan, Kepemimpinan dan Pemberdayaan - Haris Faozan (Centre for Public Policy and Management Studies, 2003)
The development of information technology and the increase of knowledge of Indonesian people are become a demand to the public service institutions to make some improvement. In fact, to make these improvement is not an easy things; in the contrary it is the, hardest thing to do. To achieve these goal leadership is mostly needed. Someone with strong leadership is needed to create empowerment for the institution and its members.